If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(2x-1)=75
We simplify the equation to the form, which is simple to understand
(2x-1)=75
Remove unnecessary parentheses
2x-1=75
We move all terms containing x to the left and all other terms to the right.
+2x=+75+1
We simplify left and right side of the equation.
+2x=+76
We divide both sides of the equation by 2 to get x.
x=38
| -(.75)(-8)(.75)(4)(1)= | | -8(1-k)=-16 | | t-11=21 | | 9-5-3+9= | | 6(1x-2)+18=-2x+46 | | X+5-1=5 | | -(.75)(-8x)(.75)(4y)(1)= | | 900=1+31n | | -5=3v+3-v | | -8(1x+4)=-112 | | 5+3t=38 | | 3*x^3-6*x^2+x-7=0 | | x^2-110-x=0 | | 2(x+1)=-2x+2 | | -8u+6(u-2)=-16 | | 0=-1x+1 | | 13(t-3)+5t=6(3t+5)-10 | | 4a-7(a+8)=-47 | | -10(1x-2)+14=4x+160 | | 7(x-3)=-42 | | 3(5-2x)-(8-6x)=-9+2(3x+4)-10 | | 6x-4=30 | | 9.2=4.4s-4 | | -2(5s-2)-4=-3(8s+0)-3 | | 3(5x+8)-2(x-6)= | | -22=-5x+13 | | Y=3(5-x) | | (x+2)=1.3*x | | [[4v-3]]=[[6v-15]] | | 4x+(-28)=0 | | 15=3(1x-3) | | (-.75)(-2x)(1.33)(0.2y)(0)= |